BURDEN MATERIAL DISCHARGE FROM THE ISOLATION BELL OF THE BLAST FURNACE CHARGING AREA (Сучасні Проблеми Металургії, 2020)
Blast furnace practice has been remaining the most suitable one in the steel production route. A rather large amount of blast furnaces (BF) is equipped with bell-like charging equipment. The discharge capability of such equipment has a drastic influence on the parameters of the charging operations and blast furnace driving rates. The charging features regulate in many cases burden materials descend and the parameters of the BF smelt. In relation to the mentioned, it is revealed that to determine the volume of the burden materials flow passing through the isolation bell of the BF charging area is an urgent scientific and engineering problem. A number of publications is devoted to the problem how to define the burden materials flow coming from the large bell. Most of these studies are grounded on the expressions by prof. Zenkov. However, there is a drawback apparently present in these findings and it can be expressed as the lack of the complex approach to incorporate such parameters as the material type, its granulometry and the geometry of the isolation bell outlet hole. The aim of the current research is to reveal the analytic dependence capable of determining the volumetric flow of the burden materials passing through the hole of the large bell. Thus, possessing the data on the burden materials flow and the geometry of the isolation bell outlet hole, one can determine the initial conditions for developing the trajectory of burden materials movement within the top area of the blast furnace. Moreover, the method proposed with the current publication permits determining the actual aggregate size of the burden materials coming to the BF top charge through the data of burden materials volumetric flow. Further, the actual size of the material particles being charged can be derived from the dependences presented in this work and this, in its turn, influences the permeability of the burden materials column for gases at a given point of BF top radius. Taking these data into account, the real opportunity emerges for an on-line correction of the BF drive by incorporating the certain on-line conditions of BF smelt. The results of the findings reported in this article are to be utilized for improvements on the automation system of blast furnace charge control.